ANALISIS POTENSI DAN PERTUMBUHAN SEKTOR EKONOMI DAERAH KABUPATEN PATI TAHUN 2020-2024 - cintia febri f (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study aims to analyze the potential and development of the regional economic sector in Pati Regency. The study was conducted using the Proportional Shift (PS) and Location Quotient (LQ) methods to measure the extent to which the regional economic sector has potential. The results of the study indicate that the sectors of Agriculture, Forestry, Fisheries, Electricity and Gas Distribution, Construction sector, Wholesale and Retail Trade, Vehicle Repair, and Financial Services and Insurance Services show positive PS values. The LQ results show an average value of >1 and are classified as basic sectors or sectors that have advantages and potential to help regional economic development. Potential sectors include, Agriculture, Forestry, Fisheries sector with an average of 1.84, Wholesale and Retail Trade, Vehicle Repair 1.07, Provision of Accommodation and Consumption 1.18, Defense and Mandatory Social Protection sector 1.20, Education Services 1.08, Health Services and Social Activities 1.17, Other Services 1.18. Sectors that produce an average value <1 will be classified as non-basic sectors such as Mining and Quarrying, Manufacturing Industry, Electricity and Gas Distribution, Water Supply, Waste and Sewage, Reprocessing, Construction sector, Transportation and Logistics sector, Information and Communication Technology Sector, Financial Services and Insurance Services, Property sector, Corporate Services.